2021
DOI: 10.1186/s13075-021-02615-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment of Behçet’s disease in the USA: insights from the Rheumatology Informatics System for Effectiveness (RISE) Registry with a comparison with other published cohorts from endemic regions

Abstract: Background Behçet’s disease (BD), a chronic systemic vasculitis, has distinct geographical and ethnic variation. Data regarding the epidemiology of patients with BD in the U.S. are limited; therefore, we sought to describe BD patient characteristics and medication use in the U.S., and compared them with data from patients from endemic regions. Methods We conducted a cross-sectional study using data from the RISE registry (2014–2018). Patients aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Indeed, the M/F ratio in BD subjects varies from 0.8 to 2.4 in the largest cohorts from the literature, with a similar frequency among men and women in most part of the world or a slight preference for males (7)(8)(9)(10)(11)(12). On the other hand, a recent epidemiology study on 1,323 patients from the US reported a 0.3 M/F ratio (13). In this context, given the methodology of this study, we cannot exclude a bias caused by the multiple recruitment channels with a preference for the spontaneous enrolment versus the traditional hospital-based one.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the M/F ratio in BD subjects varies from 0.8 to 2.4 in the largest cohorts from the literature, with a similar frequency among men and women in most part of the world or a slight preference for males (7)(8)(9)(10)(11)(12). On the other hand, a recent epidemiology study on 1,323 patients from the US reported a 0.3 M/F ratio (13). In this context, given the methodology of this study, we cannot exclude a bias caused by the multiple recruitment channels with a preference for the spontaneous enrolment versus the traditional hospital-based one.…”
Section: Discussionmentioning
confidence: 99%
“…Variants associated with AIDs are included in the 2022 classification of human inborn errors of immunity [ 18 ], many of them caused by monogenic germline or somatic mutations, and include 485 distinct disorders categorized into autoimmune, autoinflammatory, allergic, and malignant phenotypes [ 19 ]. The most well-known AID is familial Mediterranean fever (FMF), which is caused by variants in the MEFV gene [ 20 ]. It is known to be highly prevalent in the eastern Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…The well known epidemiologic features of Behçet syndrome (BS) are its high prevalence along the ancient Silk Route, increasing frequency from North to South in Europe, usual disease onset during the second decade of life, and similar frequency among men and women, but more severe disease among men. A recent study that explored demographic characteristics and prescription data in a US database between 2014 and 2018 showed that among 1324 BS patients 79% were women [32 ▪▪ ]. Glucocorticoid and biologic prescription rates were similar, suggesting similar disease severity between men and women.…”
Section: Variable Vessel Vasculitismentioning
confidence: 99%